Rekonstruksi Pendidikan Islam Modern: Analisis Pemikiran Al-Ghazali dan Fazlur Rahman - Rahmi, Laila Kamilatu; Putra, Heru Yama; Jamilus, Jamilus (Lembaga Yasin AlSys, 2025)
Although modern Islamic education has attracted considerable scholarly attention, studies that specifically synthesize the educational thought of Al-Ghazali and Fazlur Rahman to formulate a holistic and contextual model of Islamic education remain limited. This study aimed to analyze the concept of Islamic education according to Al-Ghazali, examine Fazlur Rahman’s ideas on contemporary Islamic education, and synthesize both perspectives as a basis for reconstructing modern Islamic education. The research employed a qualitative approach with a descriptive-analytical and comparative design. Data were drawn from 50 documents in the form of classical texts, books, journal articles, and relevant scholarly works selected through purposive sampling. Data were collected using document analysis and examined thematically through stages of coding, categorization, comparison, and conceptual synthesis. The findings indicate that Al-Ghazali emphasizes educational goals oriented toward the formation of insan kamil through the integration of intellect, heart, and action, whereas Fazlur Rahman stresses adaptive, contextual, and integrative education through the development of critical thinking skills and contextual understanding of religious texts. The synthesis of these two strands of thought produces a model of modern Islamic education that underscores a balance between spiritual character formation, mastery of knowledge, and adaptive capacity in responding to contemporary social challenges. These findings contribute to the development of modern Islamic educational theory by enriching an integrative framework that bridges classical tradition and neo-modernist thought, and affirm the importance of integrating spiritual, moral, and intellectual values into curricula and learning strategies that are holistic, contextual, and character-oriented. The study also opens up opportunities for further empirical research to examine the implementation of this modern Islamic education model in educational practice.